1994
DOI: 10.1152/ajplung.1994.267.1.l52
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyglucose and reduced glutathione mimic effects of hypoxia on K+ and Ca2+ conductances in pulmonary artery cells

Abstract: Hypoxia-induced pulmonary vasoconstriction (HPV) is triggered by a rise in cytosolic Ca2+ concentration ([Ca2+]i) that is partially controlled by voltage-gated Ca2+ channels. Hypoxia inhibits voltage-gated K+ (KV) channels in pulmonary artery (PA) myocytes. This depolarizes the cells, opens voltage-gated Ca2+ channels, thereby increases [Ca2+]i, and initiates HPV. In intact animals and isolated perfused lungs, metabolic inhibitors and reducing agents augment HPV. We compared the effects of hypoxia with the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 0 publications
5
62
2
Order By: Relevance
“…However, no previous isolated cell studies have shown that a 'priming' depolarization is a prerequisite for subsequent depolarization in response to hypoxia. In some studies (for example, Yuan et al 1993Yuan et al , 1994) the membrane potential in normoxic conditions was more depolarized than that observed in our study, thereby (perhaps) rendering cells sensitive to hypoxia. This difference, and the possibility that cells from different species may respond to hypoxia in a subtly different manner, could explain the discrepancy between our results and those of others.…”
Section: Synergism Between Depolarization and Hypoxiacontrasting
confidence: 50%
See 2 more Smart Citations
“…However, no previous isolated cell studies have shown that a 'priming' depolarization is a prerequisite for subsequent depolarization in response to hypoxia. In some studies (for example, Yuan et al 1993Yuan et al , 1994) the membrane potential in normoxic conditions was more depolarized than that observed in our study, thereby (perhaps) rendering cells sensitive to hypoxia. This difference, and the possibility that cells from different species may respond to hypoxia in a subtly different manner, could explain the discrepancy between our results and those of others.…”
Section: Synergism Between Depolarization and Hypoxiacontrasting
confidence: 50%
“…In our studies hypoxia was defined as an oxygen tension of between 20 and 30 mmHg. Others have on occasion used a greater degree of hypoxia (8 mmHg; Yuan et al 1994) or added dithionite (e.g. Salvaterra & Goldman, 1993;Yuan et al 1993) to scavenge and reduce PO2 levels in solution in order to obtain depolarization (note that dithionite causes a reduction of 02 with a concomitant production of superoxide anion, which itself has been reported to inhibit vascular reactivity in response to hypoxia (Archer, Hampl, Nelson, Sidney, Peterson & Weir, 1995).…”
Section: Synergism Between Depolarization and Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of K v channels being directly regulated by redox-changes has been proposed by POST et al [39]. The K v channels may be regulated by: 1) reducing agents [45][46][47][48], such as glutathione (GSH) [49]; 2) an associated haemoprotein; 3) membrane depolarisation; or 4) a calcium increase triggered by intracellular calcium release from intracellular stores or via NSCCs. Thus NSCCs may be key channels for hypoxic signalling, for example, in the regulation of potassium channels, of L-type calcium channels or the calcium level.…”
Section: Signal Transduction and Effector Mechanism: About Contractiomentioning
confidence: 99%
“…Others have alternatively shown that ROS may increase during hypoxia (Waypa et al, 2006). Inhibition of Kv currents by mETC inhibitors, particularly those acting at complexes I and III, supports this concept; at the same time, mitochondrial uncouplers, which decrease mitochondrial membrane potential (螖唯m) (Yuan et al, 1996), and metabolic inhibition of PASMCs with 2-deoxyglucose (Yuan et al, 1994) also inhibit Kv currents, suggesting the presence of multiple, presently undetermined, mitochondria-dependent mechanisms that affect Kv currents in PASMCs. Data supporting the mitochondria as an O2 sensor in PASMCs were recently published and demonstrated a mitochondrial-dependent regulation of Kv channels in PASMC, a mechanism that was absent in MASMCs and involves increased cellular Mg 2+ (Firth et al, 2008;Firth et al, 2009).…”
Section: Hypoxic Pulmonary Vasoconstriction (Hpv) and Chronic Hypoxicmentioning
confidence: 92%